Waste Heat Recovery from Exhaust Gas and Cooling Water as Water Heater on Domestic System of a Cruise Ship 48 meters - Sutopo Purwono Fitri; Agoes Santoso; Nizar Febri Anggriawan (Institut Teknologi Sepuluh Nopember, 2019)
Cruise ship is a ship used for recreational and entertainment purposes. As a means of vacation and entertainment, the design of this transportation equipment requires more attention. The design of the ship itself must be able to make it comfortable for the passengers. One way to increase comfort for cruise ship passengers is by adding heating water to the domestic system. Will need a large amount of electrical energy if you use an electric heater. While in the engine room there is exhaust heat that can be utilized. The purpose of this final project is to plan the utilization of waste heat contained in the exhaust gas and cooling water system (high temperature) as a water heater on the domestic system. The method used is analysis of calculations and references from other sources. From the results of the calculation analysis it was found that the hot water requirements of this vessel were 3409 liters/day and needed a heat 167.12 kJ/s to increase the water temperature from 250C to 660C. From the calculation results, the 50% load engine has a heat 469 kJ/s, 75% load engine has a heat 645 kJ/s, 80% load engine has a heat 729 kJ/s, 100% load engine has a heat 781 kJ/s, while in cooling water system (high temperature) has a heat 252 kJ/s. Tank insulation using glasswool with thickness 610 mm. While the insulation on the pipe uses glasswool with thickness 50 mm. By replacing electric water heater by utilizing heeat waste can be minimize the cost up to Rp. 245,211.833 per day or Rp. 7,356,355.008 per month.